Perlindungan Hukum Terhadap Merek Dagang Dalam Perspektif UU No.20 Tahun 2016 Pada UMKM : perlindungan hukum merek umkm - Tirta Ahmad Zamharir; Romi Faslah (Jurnal Ekonomi dan Bisnis Digital, 2025)
Abstract MSMEs as a small industry still assume that intellectual property protection is not important. This is evidenced by the still minimal registration of MSME Trademarks at the Directorate General of Intellectual Property. The research method used is Juridical Nominal. The results of this study are that Trademarks are one of the rights protected by IPR. Trademarks have long been used as a tool to distinguish objects and services produced by other similar companies, or are used to provide a sign of the products produced with the intention of indicating the origin of a product. The conclusion of this study is that efforts to provide brand protection for MSMEs are by registering MSME brands. Because the criteria for MSME business actors have limitations in terms of capital, assets, and annual sales results when compared to MSME businesses, the government therefore provides convenience for MSME actors to register brands, namely through a policy of cheaper MSME brand registration fees compared to Non-MSME brands, collaborating between the Directorate General of Intellectual Property Rights of the Ministry of Law and Human Rights and the Ministry of Cooperatives and MSMEs, providing incentives for financing MSME brand registration, and collective MSME brand registration. Keywords: Legal Protection, Brand, UMKM